Reinforcement of the "Rhynchospora fusca" population in the Galbaniturri mire (Izki Natural Park, Álava, Spain): first results - Infante, Marta; Heras, Patxi; Oreja, Leire; Arrieta Aseginolaza, Maialen; Garmendia Altuna, Joseba; Rubines García, Jonathan (Mediterranean Botany, 2018)
Rhynchospora fusca (L.) W.T. Aiton is a Cyperaceae that lives in constantly wet zones in acid mires, whose European distribution reaches its southernmost limit in the Spanish Cantabrian corniche. It is a characteristic plant of Habitat 7150 “Depressions on peat substrates of the Rhynchosporion” in Annex I of the EU Habitats Directive of the European Union, and also listed in the Catalogue of Threatened Species of the Basque Autonomous Community under the “Endangered” category since an only locality within the Izki Natural Park is known, in the Galbaniturri-1 mire. Given the vulnerability of this only Basque population, and aiming to improve its conservation status, a reinforcement experience was set in 2011 within LIFE+ PRO-IZKI project. We describe the main results, including the plantation at five new points in the same mire (2013 and 2015), and the monitoring for survival, flowering and fruiting for 3 consecutive reproductive periods from 2014 to 2016. The plants used for the reinforcement were vegetatively generated from plants collected in the wild. The average survival rate for the first plants planted in 2013 was very low (28%), due to the choice of planting before the winter; a second plantation in spring 2015 obtained a much higher survival rate (79%). Plant growth by rhizome renewals has been increasing year after year in almost all plots. Flowering occurred for the first time in 2016 in 6 of the 9 plots, showing heterogeneous numbers among them. Seed production has been estimated for 4 of the 6 flowering plots, also showing considerable differences. As a whole, the initial phase of reinforcement for this species is considered successful, but a final evaluation can only be made on a long-term basis.